Análisis de genes relacionados con la respuesta inmunitaria de los parásitos (trematodos) para el diseño de vacunas de ADN. - Molina Álvarez, Pamela Francisca (2020)
This research project is based on a documentary methodology, where a database of all parasites (Trematodes) of each animal species was developed, which is structured by: animal species, parasite, genomic sequence, location, gene, tissue, immunity and reference, where the information obtained may be used by biotechnologists for the development of new DNA vaccines, which will help to control parasitism in animals, thus creating an animal-specific immune response, thus controlling certain diseases, caused by these parasites. To obtain beneficial results, we searched for all kinds of information on the genetic sequence of each of the parasites in the different species: bovine, sheep, goat, equine, swine, South American camelids, lagomorphs, guinea pigs, canines, cats and birds (chicken, duck, goose and turkey). This information was obtained through the NCBI National Center for Biotechnological or National Information, a system that provided us with all the genetic information of each parasite including its sequence, letting us know the importance of the DNA segment that each of the parasites has, once all the necessary information was obtained it was possible to identify that the main genes related to immunity in the different species are: Bovine Th2, Shepp Th2, Goat Th2, IFN-γ; Porcine Th1, Th2; Equine TGF-ß, IFN-γ: Canine Th2, IFN-γ: Feline Th2: Guinea pig, Th2, IL-5; Lagomorph Th2, IFN-γ: South American camelids Th0 and Th2 IFN-γ: Birds (hen, duck, goose and turkey) Th2, IL4, IL10, IL13, T CD4 + and CD8, where the humoral type 2 immune response is considered to be the most common in trematodes, also considering that these genes are the main candidates for the development of DNA vaccines, this vaccine being in charge of generating immunity.